2023
DOI: 10.1093/gbe/evad042
|View full text |Cite
|
Sign up to set email alerts
|

Seascape Genomics and Phylogeography of the Sailfish (Istiophorus platypterus)

Abstract: Vast distances and permeable phylogeographic barriers characterize the open ocean, boosting gene flow and decreasing population structure and speciation of widely distributed and migratory species. However, many widely distributed species are formed by different populations throughout their distribution, evidencing our understanding of how the marine environment triggers population and species differentiation are insufficient. The sailfish is a circumtropical and highly migratory billfish that inhabits warm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Reid and Pinsky (2022) showed that the method exhibits ≥90% accuracy for detecting fast severe declines in population size, outperforming other methods. The method has also been applied to different sets of data from different species (Atmore et al, 2022;Bird et al, 2023;Ding et al, 2022;Ferrette et al, 2023;Pacheco et al, 2022;von Seth et al, 2022;Wersebe & Weider, 2023). However, the simulation tests have always a restricted scope, as the models simulated cannot encompass all the complexities of real genomes.…”
mentioning
confidence: 99%
“…Additionally, these approaches have been applied to several commercially important fish species, including hake (Milano et al, 2014), herring (Limborg et al, 2012), seabream and mullet yellowtail (Mendoza-Portillo et al, 2023). While there has been considerable focus on certain species such as dolphins (Barcelo et al, 2022;Pratt et al, 2022;Wittwer et al, 2023) and sailfish (da Silva Ferrette et al, 2023), seascape genomics has seen limited application in elasmobranchs, with only two studies focusing on the blue skate Dipturus batis (Delaval et al, 2022) and the copper shark Carcharhinus brachyurus (Klein et al, 2024). Nonetheless, these studies highlight the potential of highly heterogeneous seascapes to contribute to adaptive divergence, especially in populations exhibiting resident and philopatric tendencies, driven by ecologically divergent selection pressures (Portnoy et al, 2015;Pratt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of estimating changes in population size in the recent past is particularly useful in livestock species, for which the start of breeding programs may imply substantial changes in N e . To date, this software has been applied to various breeds of pigs [ 20 ], cattle [ 21 , 22 ], sheep [ 23 , 24 ], horses [ 25 ] and chickens [ 26 , 27 ], and fish species such as turbot, seabream and seabass [ 16 ], Baltic herring [ 28 ], pikeperch [ 29 ], coho salmon [ 30 ], catfish [ 31 ] and sailfish [ 32 ].…”
Section: Introductionmentioning
confidence: 99%